Utilising information and communication technology to enhance writing skills in English first additional language : two secondary schools, Kgakotlou Circuit - Mengwai, Tonny Kolo (My University, 2022)
The primary aim of the study was to investigate ways in which learning and teaching of English First Additional Language writing skills can be taught through Information and Communication Technology. Four teachers from School A were interviewed and Four teachers from School B were observed. Six learners typed letters from School A, and six wrote essays from School B. The results indicated that learners and teachers from School A had more knowledge in incorporating Information and Communication Technology(ICT) into teaching and learning writing skills, and that also improved their performance. School B, due to lack of ICT skills in EFAL writing skill, resulted in learners committing errors and indicating a distress to teachers in their learning and teaching of EFAL writing skills. Nonetheless, the recommendations were clearly stated that teachers should be given sufficient training, especially from School B, regarding the application of ICT through teaching English writing skills. It should be every teacher, learner, and parent’s responsibility to monitor and assist their learners through ICT learning. Lastly, relevant policies should be drafted to make ICT compulsory in learning and teaching language, together with provision of resources to support this new norm of learning and teaching.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2022
Keywords: Technology; Writing skill; Communication; Teaching; Learning; Information; English language -- Study and teaching; Communication of technical information; English language -- Writing